PEMBERDAYAAN LANSIA DALAM MENINGKATKAN KETAHANAN PANGAN DI PANTI SOSIAL LANJUT USIA HARAPAN KITA - Santoso, Budi; Anita, Sumarni Bayu; Pusnita, Indah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2023)
Law Number 13 of 1998 concerning the Welfare of the Elderly defines the elderly population as those who have reached the age of 60 (sixty) years and over. The elderly empowerment activity uses a participatory implementation method, namely by inviting all elderly people of productive age to take part in activities carried out at the Harapan Kita Social Home, Palembang City, starting from the planning and data collection process to preparing the framework for practical field work activities, and the activities have been carried out for 1 ( one month. Elderly empowerment activities consist of several activity stages starting from the planning stage, the implementation stage, there are two main activities, namely vegetable cultivation and catfish cultivation as well as making chocolate characters, and the activity evaluation stage. This activity has a positive impact not only for the elderly but also for service institutions involved in empowering the elderly, including improving physical well-being, encouraging the elderly to remain socially active, participate in community activities, and maintain healthy social relationships and increase the independence of the elderly and reduce dependence on other parties.